(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The experiment was carried out to examine the possibilities of making compost by using layer litter with different bulking materials and to assess the nutritive value of compost. To fulfill the objectives five treatments were considered e.g., anaerobic composting with layer litter (T1), layer litter with straw (T2), layer litter with tree leaves (T3), layer litter with crop residues (T4) and layer litter with saw dust (T5) under soil surface. The samples from composted materials were collected at 0, 10, 20 and 30 days for proximate analysis. At 0 day of layer litter composting DM content did not vary significantly (p>0.01) var ied in all treatments.. At 10 day of layer litter composting DM content was the highest in T4 (50.0%) and CF content was the highest in T2 (22.2%). CP content remained similar varied in all treatments. At 20 day of layer litter composting DM content was highest in T4 (51.5%), CP content was the highest in T4 (19.5%), CF content was the highest in T2 (18.0%), Ash content was the highest in T4 (18.5%). At 30 day of layer litter composting DM content was the highest in T2 (51.1%) and CP content was the highest in T4 (17.6%). The pH value decreased upto first tendays then gradually increased with the composting period and highest value was obtained by T1 (8.40) then followed by T2 (8.20), T3 (8.15), T5 (8.10) and T4 (8.00) (p<0.01) at 30 d of composting. The C/N ratios increased (p<0.01) in all treatments with the advancing of composting period and highest value was obtained in T4 (27.9) followed by T1 (26.7), T5 (26.3), T3 (26.2) and T2 (25.3) considerably with the composting period. So, it may be concluded that proximate composition of all samples at 20 days in T4 treatment was acceptable up to the end of composting period. However, composting layerlitter with crop residues (T4) was more effective compare to other treatments at 20 days of composting in terms of Dry matter, CP content, C/N ration and pH. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22054 J. Environ. Sci. & Natural Resources, 6(1): 141-144 2013